POLSZCZYZNA RADZIECKA NA KARTACH SŁOWNIKA ROSYJSKO-POLSKIEGO JÓZEFA KRASNEGO - Sobczak, Michał (Acta Neophilologica, 2016)
This article concerns a specific language-code that was used by the Poles living in the territory of the Soviet Union in the interwar period. The introductory section outlines the history of the Polish minority in the USSR, discusses the major premises of the ethnic policy of the Soviet authorities employed with respect to ethnic minorities and presents the features of the Soviet Polish language. The empirical section is focused on the analysis of the entries from the Russian-Polish dictionary of Józef Krasny. It is established that the equivalents of the Russian units placed in this dictionary are classified to the Soviet Polish language. This aspect is seen on the lexical, inflective and syntactic grounds.